(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study describes the current nursing care situation at Khoai Chau District Medical Center, Hung Yen Province in 2024. Participants and Methods: A cross-sectional study was conducted at Khoai Chau District Medical Center, with the participation of 196 patients and their family members. Results: Among the five aspects of patient care assessed, all achieved a satisfaction rate of over 90%, with patient reception receiving the highest rating at 94.9%. Two additional aspects of patient care were rated above 80%, with health education and communication receiving the lowest score at 83.2%. Conclusion: It is recommended that the patient reception process be maintained and further enhanced while continuing to implement professional and nursing technical procedures. Special attention should be given to patient care in respiratory function, circulation, and body temperature management. Additionally, nurses should focus on improving health education communication and rehabilitation processes to ensure comprehensive patient care.